QT prolongation after ampicillin anaphylaxis. Issue 3 (March 1986) - Mehta, D; Warwick, G L; Goldberg, M J
Abstract : Tall T waves and pronounced prolongation of the QT interval developed 24 hours after an apparently complete recovery from an acute anaphylactic reaction to oral ampicillin in a previously healthy woman of 29. These electrocardiographic abnormalities gradually subsided over five days. The prolongation of the QT interval has not previously been reported after anaphylaxis.